2014
DOI: 10.1371/journal.pone.0090848
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptotic Effect of D Rhamnose β-Hederin, a Novel Oleanane-Type Triterpenoid Saponin on Breast Cancer Cells

Abstract: There is growing interest in development of natural products as anti-cancer and chemopreventive agents. Many triterpenoids have been proved as potential agents for chemoprevention and therapy of breast cancer. Ginsenosides from ginseng, which mostly belong to dammarane-type triterpenoids, have gained great attention for their anti-breast cancer activity with diverse mechanisms. However, studies of other kinds of triterpenoid saponins on breast cancer are limited. Previously, we purified and identified a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
(59 reference statements)
1
28
0
Order By: Relevance
“…This was based on MTT assay results and confirmed with flow cytometry analysis of cancer cells incubated with different concentrations of DRβ-H. It was previously reported that DRβ-H regulated the phosphoinositide 3-kinase/AKT serine threonine kinase signaling pathway and activated pro-apoptotic proteins of the B cell lymphoma-2 family ( 5 ). No apoptosis-associated signaling pathways were examined in the present study, and it will be necessary to investigate the concrete pathways involved in proliferation inhibition.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This was based on MTT assay results and confirmed with flow cytometry analysis of cancer cells incubated with different concentrations of DRβ-H. It was previously reported that DRβ-H regulated the phosphoinositide 3-kinase/AKT serine threonine kinase signaling pathway and activated pro-apoptotic proteins of the B cell lymphoma-2 family ( 5 ). No apoptosis-associated signaling pathways were examined in the present study, and it will be necessary to investigate the concrete pathways involved in proliferation inhibition.…”
Section: Discussionsupporting
confidence: 76%
“…A large number of active components purified from natural plants have been used to treatvarious tumors including breast cancer ( 2 , 3 ). The authors' previous study demonstrated that DRβ-H, a noveloleanane-type triterpenoid saponin derived from Clematis ganpiniana , exhibited apotentinhibitory effecton breastcancer cells ( 5 ). In the present study, it was reported that DRβ-H may inhibit breast cancer cell growth by remodeling the tumor microenvironment via reducing exosome release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, DRβ-H regulated the ratio of proapoptotic and antiapoptotic Bcl-2 family proteins. Furthermore, DRβ-H induced depolarization of mitochondrial membrane potential which released Apaf-1 and Cytochrome C from the inter membrane space into the cytosol, where they promoted caspase-9 and caspase-3 activation[51]. Han et al isolated five oleanane type triterpenoid saponins glycoside ST-14a, glycoside ST-J, anhuienoside E, hedra saponin B and flaccidoside II from the rhizome of Anemone flaccida and evaluated for antitumor activity on human BEL-7402 and HepG2 hepatoma cell lines, as well as the model of cervical tumor cells (HeLa) treated with lipopolysaccharide (LPS).…”
mentioning
confidence: 99%